Study of Adsorption Kinetics and Degradation of Fatty Oil in Palm Oil Mill Effluent (POME) Using Activated Bentonite - Sunartaty, Rita; Sufriadi, Elly; Saiful, Saiful (Universitas Syiah Kuala, 2024)
A study was conducted on the treatment of palm oil liquid waste using activated bentonite through an adsorption method. Four variations of adsorbent treatments were employed: untreated bentonite (UBA), and chemically activated bentonite with 5%, 10%, and 15% H2SO4 (CAB-5, CAB-10, and CAB-15, respectively). The adsorption capacities (qe) for UBA, CAB-5, CAB-10, and CAB-15 were found to be 91.01, 97.01, 94.46, and 93.27 mg/g, respectively. The adsorption kinetics followed a first-order reaction model, with correlation coefficients (R2) of 0.70, 0.93, 0.98, and 0.94 for UBA, CAB-5, CAB-10, and CAB-15, respectively. Additionally, the fatty oil content of the treated waste, when adsorbed for 60 to 100 minutes, met the quality standard threshold, reducing it to below 25 mg/L. This study underscores the importance of addressing the waste produced by the palm oil industry and emphasizes the need for effective effluent treatment to protect the environment and ensure industry sustainability.